Overexpression of MMP14 is associated with poor prognosis and immune cell infiltration in colon cancer - Li, Na; Zhang, Nan; Wang, Guanghui (Frontiers in Oncology, 2025)
IntroductionColorectal cancer (CRC) poses a significant risk of recurrence and distant metastases. This study investigated the regulatory role of Matrix metalloproteinase-14 (MMP14) in immune function and its impact on CRC prognosis.Methodswe performed transcriptome sequencing on tumor and adjacent non-cancerous samples from four pairs of patients diagnosed with colorectal cancer. Single-cell transcriptome data were analyzed to explore MMP14 expression and immune microenvironment changes. mRNA expression profiles and clinical data were retrieved from public databases (TCGA and GEO). The association between MMP14 and pathways as well as immune regulators was analyzed. Co-expression genes of MMP14 relevant to prognosis were identified. A prognostic model was then constructed. MMP14 expression was examined using real-time fluorescence quantification PCR (qRT-PCR) and Western blotting (WB). Immunofluorescence was utilized to demonstrate MMP14 expression in colon cancer tissues, while Hematoxylin and eosin (HE) staining was employed to observe the histology of normal tissue and colon cancer tissue.ResultsMachine learning identified MMP14 as a candidate gene. MMP14 was overexpressed in CRC tissues and COLO205 cells. Single-cell transcriptome analysis revealed that MMP14 was highly expressed in fibrocyte cells within the liver metastasis group. Increased MMP14 levels correlated with poor overall survival (OS), progression-free survival (PFS), and advanced TNM stages. Functional assays indicated that silencing MMP14 in COLO205 cells enhanced apoptosis and upregulated the expression of the immune-related cytokine IL-1β. Furthermore, MMP14 exhibited significant correlations with immunomodulators, particularly immunostimulants and immunosuppressants, and was associated with immune cell infiltration within tumor tissues. Additionally, by utilizing co-expressed genes of MMP14 and conducting Cox regression analysis, we developed a risk prediction model comprising three genes (LIMK1, SPOCK3, SLC2A3). The risk scores derived from this model were found to correlate with OS and PFS.DiscussionMMP14 plays a crucial role in CRC progression. Its overexpression is related to poor prognosis and immune cell infiltration. The prognostic model based on MMP14 co-expression genes may help predict CRC prognosis. However, further studies are needed to validate these findings, such as more in-vitro and in-vivo experiments. In conclusion, MMP14 can serve as a biomarker for evaluating CRC prognosis and immune cell infiltration.